Loss of Elbow Flexion in Congenital Arthrogryposis Treated with a Bipolar Latissimus Transfer: A Case Report. Issue 3 (14th July 2020) - Stein, Matthew; Ashley, Blair; Falk, David; Gittings, Daniel; Glaser, David; Levin, Lawrence Scott
Abstract : Case: A 20-year-old man with congenital arthrogryposis presented for evaluation of biceps dysfunction. Although his left elbow was supple with 0° to 110° passive range of motion (ROM), he had no active ROM and was unable to perform basic activities of daily living such as bringing his hand to his mouth to feed himself. A bipolar latissimus transfer was performed to achieve functional active ROM. Conclusion: Bipolar latissimus transfer is a challenging, robust flap able to restore active elbow flexion in select groups of patients with biceps dysfunction, supple elbow, and functional latissimus dorsi.